Baseline characteristics in the Collaborative AtoRvastatin Diabetes Study (CARDS) in patients with Type 2 diabetes. - Thomason, M; Colhoun, H; Livingstone, S; Mackness, M; Betteridge, D; Durrington, P; Hitman, G; Neil, H; Fuller, J (2004)
AIM: To describe baseline characteristics of patients in the Collaborative AtoRvastatin Diabetes Study (CARDS), a randomized, placebo-controlled trial of lipid lowering with atorvastatin 10 mg daily for the primary prevention of major cardiovascular events in patients with Type 2 diabetes. METHODS: The main eligibility criteria were Type 2 diabetes, age 40-75 years, no previous history of coronary heart disease, stroke or other major cardiovascular events, a documented history of at least one of retinopathy, micro- or macroalbuminuria, hypertension or current smoking, LDL-cholesterol < or = 4.14 mmol/l and triglycerides < or = 6.78 mmol/l. RESULTS: Randomization of 2838 persons (909 women) into CARDS was completed in June 2001. At entry, mean age was 62 years, 12% were over 70 years old and median duration of diabetes was 6 years. Median fasting lipid levels were total cholesterol 5.4 mmol/l, LDL-cholesterol 3.1 mmol/l, HDL-cholesterol 1.4 mmol/l and triglyceride 1.7 mmol/l. There was a documented history of retinopathy in 30% of patients, micro/macroalbuminuria in 11% (additionally 17% had micro/macroalbuminuria based on two elevated pretreatment measurements of albumin-creatinine ratios), hypertension in 79% and 23% were current smokers. CONCLUSION: CARDS will contribute importantly to the evidence for the macrovascular and microvascular benefits of lipid lowering with atorvastatin in patients with Type 2 diabetes. The results are likely to have important implications for the management of patients.